Développement et fragmentation d’une ville moyenne en cours de mondialisation : le cas de Salalah (Oman) - Steffen Wippel (Arabian Humanities, 2013)
To study the current economic and spatial reconfiguration of the city of Salalah in Southern Oman means to analyse one of the “secondary cities” on the Arab side of the Gulf. These have been neglected compared to the interest shown for several years now for major cities. Salalah only appeared on the economic world map after its container port was built in the late 1990s. In addition, further major industrial, tourism and infrastructural projects are currently being developed. The article endeavours to understand to which extent Salalah nowadays is to be apprehended as a “globalising” city and how it is developing features considered characteristic for “postmodern” cities as well as for contemporary port cities. The fragmentation of the current urban agglomeration is of particular interest, as it mainly results from projects allowing only limited access, more integrated into the global rather than the local economy.